Share

# If X = Pab/(A+B) , Then Prove that (X + Pa)/(X - Pa) + (X + Pb)/(X - Pb) = 2(A2 - B2)/Ab - ICSE Class 10 - Mathematics

#### Question

If x = "pab"/("a + b"), then prove that ("x + pa")/("x - pa") + ("x + pb")/("x - pb") = (2("a"^2 - "b"^2))/"ab"

#### Solution

x = "pab"/("a + b") => "x"/"pa" = "b"/("a + b")

Applying componendo and dividendo

("x + pa")/("x - pa") = ("b + a + b")/("b - a - b") = ("2b + a")/"- a"   .............(i)

Again , x = "pab"/("a + b") => "x"/"pb" = "a"/("a + b")

Applying componendo and dividendo

("x + pb")/("x - pb") = ("a + a + b")/("a - a - b") = ("2a + b")/"- b"   .............(ii)

("x + pa")/("x - pa") + ("x + pb")/("x - pb") = ("2b + a")/"- a" +("2a + b")/"- b" = ("a - 2"b"")/"a"  + ("b - 2a")/"b"

= (-2"b"^2 + "ab" - 2"a"^2 + "ab")/"ab"

= (-2"b"^2 + 2 "ab" - 2"a"^2)/"ab"

= (2 ("a"^2 - "b"^2))/"ab" = 2 = RHS

LHS = RHS

Hence proved.

Is there an error in this question or solution?

#### APPEARS IN

Frank Solution for Frank Class 10 Mathematics Part 2 (2016 to Current)
Chapter 9: Ratio and Proportion
Exercise 9.3 | Q: 14

#### Video TutorialsVIEW ALL [1]

Solution If X = Pab/(A+B) , Then Prove that (X + Pa)/(X - Pa) + (X + Pb)/(X - Pb) = 2(A2 - B2)/Ab Concept: Ratio and Proportion Example.
S